Pro-fertility and Antioxidant Potentials of Vigna unguiculata (Cowpea) Protein Isolate and Essential Oil: An In vivo and In silico Studies - Oladimeji, Olugbenga Samuel; Awote, Olasunkanmi Kayode; Elum, Nzubechi Olympian (Protein and Peptide Letters, 2025)
IntroductionVigna unguiculata (Cowpea), a legume rich in phytochemicals, has been traditionally used to improve fertility and treat various ailments. This study used in-silico and in- vivo methods to evaluate the effects of cowpea protein isolate and essential oil on reproductive hormonal and antioxidant indices.MethodsForty (40) female rats were divided into eight groups (n=5). After 14 days of treatment, hormone levels (progesterone, prolactin, testosterone and estradiol) and antioxidant activities (superoxide dismutase (SOD), catalase (CAT) were assessed using biochemical kits and standard procedures. Molecular docking studies were performed using PyRx and Biovia Discovery Studio 2021. The ligands generated through gas chromatography-mass spectroscopy (GCMS) analysis of cowpea oil and the target proteins (SOD and CAT) were from downloaded PubChem and RCSB Protein Data Bank, respectively.ResultsThe results of this study showed that cowpea essential oil and protein isolate significantly (p<0.05) reduced plasma CAT and SOD activities while increasing their activities in the ovary and liver tissues compared to the infertile untreated group. Consistent administration of either cowpea oil or protein isolate was observed to positively regulate the hormonal indices in the infertile treated groups. Phthalic acid, 2-cyclohexyl ethyl isobutyl ester demonstrated a strong binding affinity and binding constant with SOD and CAT, which suggests that the ligands from cowpea essential oil may have antioxidant and pro-fertility properties that could be developed to treat fertility-related issues.ConclusionBased on the results of this study, it can be concluded that V. unguiculata has antioxidant property, and can promote fertility, possibly through its rich embedded phytochemicals, which substantiates its traditional claim.
Keywords: pro-fertility